STRATEGI PERUSAHAAN UNTUK MENINGKATKAN KESEJAHTERAAN PEKERJA MENGGUNAKAN SISTEM PREMI DALAM PENGUPAHAN BURUH HARIAN SKALA UMKM PADA USAHA PERCETAKAN DI SURABAYA BARAT - Mardiana Sukendah Hariati; Woro Utari; Muninghar Muninghar (Prodi Magister Manajemen Universitas Wijaya Putra, 2017)
This study aims to determine the description of the company's strategy to improve the welfare of workers using a system of premiums in the wage of day-scale workers of UMKM on Printing Business in West Surabaya. By describing how premium wages can improve the welfare of daily laborers in the printing business of West Surabaya, especially the areas of Petemon, Manukan and Sambikerep. The researcher focuses on printing business of UMKM scale, where their business capital is small and has a small number of workers. The type of research used is descriptive by using qualitative approach. The data sources used consist of primary data and secondary data. Data collection techniques used were interviews. Data analysis technique used is qualitative data analysis technique. The result of the research shows that printing company strategy of UMKM scale in West Surabaya especially in Petemon, Manukan and Sambikerep area in improving the welfare of daily worker using premium system besides daily wage.